Avaliação da concordância dos limiares metabólicos por meio de três métodos diferentes de identificação - Neves, Letícia Nascimento Santos (2019)
Metabolic thresholds are physiological intensity markers, important in the evaluation and prescription of physical exercises, and can be determined through several variables, among them lactacidemia, ventilatory parameters and, more recently, heart rate variability (HRV). Lactacidemia and ventilatory parameters are further consolidated in the literature as independent markers of metabolic thresholds. However, when it comes to HRV there is still inconsistency in the results of the studies, mainly with the use of different interpretative variables. This complicates its practical application, not allowing to conclude that the methods (lactate threshold 1 and 2, ventilatory threshold 1 and 2, but mainly the heart rate variability threshold 1 and 2) could be used interchangeably. Thus, this investigation aims to evaluate the agreement between the three identification methods of metabolic thresholds 1 and 2. The sample consisted in 34 participants, young adults (± 22 years), university students, male. The procedures were divided into two visits to the laboratory. Initially, anamnesis data and anthropometric measures were collected. The cardiopulmonary exercise test (CPx) with ramp protocol until exhaustion was performed to identify the ventilatory threshold, and to estimate the speed at which the step test started. After 48h, the second test was performed, the stepwise progressive test (TPE) composed 3 min stages to identify the metabolic thresholds. Manova was used to compare means between methods, followed by Sidak post-hoc. Pearson's correlation was applied to verify association between the methods. The coefficient of variation (CV) and typical error (TE) were used to verify variability and precision, the intraclass correlation coefficient (ICC) and Bland Altman to evaluate reliability and agreement. The results revealed that at threshold 1, although acceptable concordances were found, the variability values were high and the reliability low. On the other hand, at threshold 2, good agreement, acceptable variability and high reliability were found. Therefore, based on the results, three methods can be used interchangeably/independently at threshold 2, however at threshold 1 showed controversial, but can be used as an auxiliary tool in the identification of the threshold 1.